1997
DOI: 10.1126/science.278.5342.1464
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Invasion of Epithelial Cells by Tiam1-Rac Signaling

Abstract: Tiam1 encodes an exchange factor for the Rho-like guanosine triphosphatase Rac. Both Tiam1 and activated RacV12 promote invasiveness of T lymphoma cells. In epithelial Madin-Darby canine kidney (MDCK) cells, Tiam1 localized to adherens junctions. Ectopic expression of Tiam1 or RacV12 inhibited hepatocyte growth factor-induced scattering by increasing E-cadherin-mediated cell-cell adhesion accompanied by actin polymerization at cell-cell contacts. In Ras-transformed MDCK cells, expression of Tiam1 or RacV12 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

33
330
2
1

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 415 publications
(366 citation statements)
references
References 23 publications
33
330
2
1
Order By: Relevance
“…In breast tumor cells, such as SP-1 cells, Tiam1 is detected as a 200-kD protein (Fig. 1), which is similar to the Tiam1 described in other cell types (Woods and Bryant 1991; Michiels et al 1995; Nobes and Hall 1995; Van Leeuwen et al 1995, Van Leeuwen et al 1997; Hordijk et al 1997; Stam et al 1997; Bourguignon et al 2000). Tiam1, isolated from SP-1 cells, is also capable of carrying out GDP/GTP exchange for Rac1 in vitro (Fig.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…In breast tumor cells, such as SP-1 cells, Tiam1 is detected as a 200-kD protein (Fig. 1), which is similar to the Tiam1 described in other cell types (Woods and Bryant 1991; Michiels et al 1995; Nobes and Hall 1995; Van Leeuwen et al 1995, Van Leeuwen et al 1997; Hordijk et al 1997; Stam et al 1997; Bourguignon et al 2000). Tiam1, isolated from SP-1 cells, is also capable of carrying out GDP/GTP exchange for Rac1 in vitro (Fig.…”
Section: Discussionsupporting
confidence: 64%
“…Rac1 acts downstream of Tiam1 signaling and regulates the function of several cell adhesion molecules such as the laminin receptor, α6β1 integrin (Van Leeuwen et al 1997), E-cadherin (Hordijk et al 1997), and the hyaluronan receptor, CD44 (Bourguignon et al 2000). Tiam1-Rac1 activation also has been shown to be stimulated by certain serum-derived growth activators (e.g., S1P and LPA) during T-lymphoma cell invasion (Stam et al 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the small GTPase Rac-1 in epithelial cell proliferation and transformation has not been well characterized and may be cell type-dependent. It has been recently shown that Val-12 Rac can partially revert Ras-induced transformation of epithelial kidney cells, by promoting E-cadherin-mediated cell-cell adhesion (Hordijk et al 1997). On the other hand, in mammary epithelial cells Val-12 Rac has been shown to disrupt normal polarization and promote integrinmediated cell motility and invasiveness (Keely et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Rac regulates formation of lamellipodia and membrane ru ing in various types of cultured cells (for reviews, see Hall, 1994Hall, , 1998. Rac regulates actin assembly at the adherens junction of the wing disc epithelium in Drosophila (Luo et al, 1994;Eaton et al, 1995), the formation of cadherin-dependent cell-cell adhesion in MDCK cells and human keratinocytes (Braga et al, 1997;Hordijk et al, 1997;Takaishi et al, 1997;, and tight junction in MDCK cells . Cdc42 regulates the formation of ®lopodia in various types of cells (for review, see Hall, 1998).…”
Section: Introductionmentioning
confidence: 99%